2008
DOI: 10.1016/j.yebeh.2008.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Thought disorder and frontotemporal volumes in pediatric epilepsy

Abstract: The aim of this study was to determine if volumes of frontotemporal regions associated with language were related to thought disorder in 42 children, aged 5-16 years, with cryptogenic epilepsy, all of whom had complex partial seizures (CPS). The children with CPS and 41 age-and gender-matched healthy children underwent brain MRI scans at 1.5 T. Tissue was segmented, and total brain, frontal lobe, and temporal lobe volumes were computed. Thought disorder measures, IQ, and seizure information were collected for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…However, for patients with SW epileptic seizures, it is very possible that the relative connectivity strength and fiber length are varied. Recently, cross-sectional studies of children, adolescents and young adults with idiopathic generalized epilepsies (IGE) including childhood absence and juvenile myoclonic epilepsy have reported distributed patterns of abnormality predominantly affecting thalamus and frontal lobe (Betting et al, 2006a(Betting et al, , 2006b(Betting et al, , 2006cCaplan et al, 2009aCaplan et al, , 2009bde Araujo et al, 2009;Kim et al, 2007;Pardoe et al, 2008;Pulsipher et al, 2009;Tae et al, 2006Tae et al, , 2008Tosun et al, 2011). Collectively, these studies clearly indicate a neurodevelopmental contribution to anatomic abnormalities that have been observed in adults with these syndromes of epilepsy ).…”
Section: White Fiber Abnormalitymentioning
confidence: 98%
“…However, for patients with SW epileptic seizures, it is very possible that the relative connectivity strength and fiber length are varied. Recently, cross-sectional studies of children, adolescents and young adults with idiopathic generalized epilepsies (IGE) including childhood absence and juvenile myoclonic epilepsy have reported distributed patterns of abnormality predominantly affecting thalamus and frontal lobe (Betting et al, 2006a(Betting et al, , 2006b(Betting et al, , 2006cCaplan et al, 2009aCaplan et al, , 2009bde Araujo et al, 2009;Kim et al, 2007;Pardoe et al, 2008;Pulsipher et al, 2009;Tae et al, 2006Tae et al, , 2008Tosun et al, 2011). Collectively, these studies clearly indicate a neurodevelopmental contribution to anatomic abnormalities that have been observed in adults with these syndromes of epilepsy ).…”
Section: White Fiber Abnormalitymentioning
confidence: 98%
“…Most notably, these studies have identified significantly different relationships of language measures with brain volumes and cortical thickness and depth in children with epilepsy compared to typically developing age and gender matched children. They demonstrate that both children with epilepsy with and without impaired language skill have abnormal development and reorganization of language-related brain regions including the inferior frontal gyrus, posterior superior temporal gyrus, temporal lobe, Heschl’s gyrus, orbital frontal gyrus, and dorsolateral prefrontal cortex (32, 33) (See brain regions in Figure 1). …”
Section: Language and Imaging In Pediatric Epilepsymentioning
confidence: 99%
“…In healthy children, however, these measures were related to significantly larger orbital frontal gyrus, superior temporal gyrus, and temporal lobe gray matter volumes, as well as to decreased Heschl’s gyrus white matter volumes (32). …”
Section: Language and Imaging In Pediatric Epilepsymentioning
confidence: 99%
“…Furthermore, psychiatric comorbidity in children with epilepsy is significantly more prevalent than in children with other chronic health conditions (Caplan et al 2008; Jones et al 2008; for a review see Plioplys et al 2007). …”
Section: Introductionmentioning
confidence: 99%